Effects of grazing management on leaf area and total nonstructural carbohydrates of dwarf elephantgrass - Rodrigues, Luís Roberto de A.; Mott, Geraldo O.; Veiga, Jonas B.; Ocumpaugh, William R. (Pesquisa Agropecuaria Brasileira, 2014)
Effects of grazing management on leaf arca and total nonstructural carbohydrates (TNC) of dwarf elephantgrass (Pennisetum purpureum) were studied in a grazing trial conducted in 1982 at the University of Florida, Gainesville, FL, USA. Two grazing management factors were studied as experimental variables: a) length of grazing cycle (GC), and b) grazing pressure (GP). The grass was subjected to five levels of each of these variables as follows: GC - continuous graring, 14, 28.42 and 56 days; and GP - 500, 1,000, 1,500, 2,000 and 2,500 kg of residual leaf dry matter h-1 (RLDM ha-1). Response surface methodology was used to analyse the data. The average number of leaves per main tiller was greater when long grazing cycles were combined with low grazing pressures. The number of senescent leaves per main tiller increased as the grazing cycle was increased. Leaf area of green leaf blades increased as the GC increased and the GP decreased. Concentrations of TNC in stem bases of the grass were affected mainly by the length of GC and were lower at short GCs and high GPs. The physiological responses observed indicate that short grazing cycles and high grazing pressures should be avoided in the management of dwarf elephantgrass.